(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article is devoted to the issue of developing mathematical competence among primary school students. Mathematical competence plays an essential role in helping students acquire mathematical knowledge, develop logical thinking, and enhance problem-solving skills. The use of modern pedagogical methods — such as problem-solving strategies and logical tasks — provides opportunities for students to expand their worldview through mathematics.